Colloidal stability of nanosized activated carbon in aquatic systems: Effects of pH, electrolytes, and macromolecules. (15th September 2021) - Shao, Zhiwei; Luo, Shijie; Liang, Miaoting; Ning, Zengping; Sun, Weimin; Zhu, Yujing; Mo, Juncheng; Li, Yongtao; Huang, Weilin; Chen, Chengyu
Highlights: Increasing pH from 4 to 9 stabilized NAC by raising CCC value from 28 to 590 mM NaCl. Cations destabilized NAC following the order of Ba 2+ > Ca 2+ > Mg 2+ >> Na + > K + . Macromolecules stabilized NAC following the order of EPS > BSA > CEL > HA > FA > ALG. ALG and HA destabilized NAC via cation bridging with Ca 2+ at high concentrations. Near half of NAC remained stable suspended for ∼10 d in neutral freshwater samples. Abstract: Nanosized activated carbon (NAC) is a novel adsorbent with great potential for water reclamation. However, its transport and reactivity in aqueous environments may be greatly affected by its stability against aggregation. This study investigated the colloidal stability of NAC in model aqueous systems with broad background solution chemistries including 7 electrolytes (NaCl, NaNO3, Na2 SO4, KCl, CaCl2, MgCl2, and BaCl2 ), pH 4–9, and 6 macromolecules (humic acid (HA), fulvic acid (FA), cellulose (CEL), bovine serum albumin (BSA), alginate (ALG), and extracellular polymeric substance (EPS)), along with natural water samples collected from pristine to polluted rivers. The results showed that higher solution pH stabilized NAC by raising the critical coagulation concentration from 28 to 590 mM NaCl. Increased cation concentration destabilized NAC by charge screening, with the cationic influence following Ba 2+ > Ca 2+ > Mg 2+ >> Na + > K + . Its aggregation behavior could be predicted with the Derjaguin-Landau-Verwey-Overbeek (DLVO) theory with a Hamaker constant ( A CWC ) of 4.3 × 10 −20 J. The presence of macromolecules stabilized NAC in NaCl solution and most CaCl2 solution following EPS > BSA > CEL > HA > FA > ALG, due largely to enhanced electrical repulsion and steric hindrance originated from adsorbed macromolecules. However, ALG and HA strongly destabilized NAC via cation bridging at high Ca 2+ concentrations. Approximately half of NAC particles remained stably suspended for ∼10 d in neutral freshwater samples. The results demonstrated the complex effects of water chemistry on fate and transport of NAC in aquatic environments. Graphical abstract: Image, graphical abstract